Chemical Process Dynamics and Controls - Woolf, Peter J. (Open textbook library., 2009)
Process controls is a mixture between the statistics and engineering discipline that deals with the mechanism, architectures, and algorithms for controlling a process. Some examples of controlled processes are: •Controlling the temperature of a water stream by controlling the amount of steam added to the shell of a heat exchanger. •Operating a jacketed reactor isothermally by controlling the mixture of cold water and steam that flows through the jacket of a jacketed reactor. •Maintaining a set ratio of reactants to be added to a reactor by controlling their flow rates. •Controlling the height of fluid in a tank to ensure that it does not overflow.